Effect of essential oils of clove and cumin against the growth of Staphylococus Aureus isolated from Denture Stomatitis - M., Minasari (Padjadjaran Journal of Dentistry, 2016)
Background: Essential oils of clove and cumin had an inhibition effect against Staphylococcus aureus. Cloveâs essential oils has a compound named eugenol, which can directly damage the membrane cell of bacteria. Thymoquinone, the active ingredient in the black cuminâs essential oils inhibits the protein synthesis and cause malfunction of the bacterial cell. The purpose of this research was to determine the differences of inhibitory effect from essential oils of cloves and cumin to the growth of Staphylococcus aureus. Method: This research was an experimental laboratory with Post-test Only Control Group Design. Sample that being used for this experiment was Staphylococcus aureus that had been isolated from a denture stomatitis patient. This inhibition test was determined using a Disc Diffusion Testâs method with the essential oils of clove and cumin, while distilled water and 96% ethanol as a negative and positive control, respectively. Essential oils were obtained from the distillation method with water and steam and the test was done 7 times repetition with every ingredients. Inhibition zone was measured with a vernier calipers. The data were analyzed by ANOVA One-way test followed by a multiple comparison test. Result:Â  The average zone of inhibition against Staphylococcus aureus from aquades 0 mm, 96% ethanol 13.894 mm, the essential oils of clove 14.784 mm and black cumin 11.944 mm. The multiple comparison test analysis showed a significant differences (p <0.05) between the average zone of inhibition of the materials tested. Conclusion: Clove essential oil has a greater inhibition against Staphylococcus aureus than the essential oils of cumin.